2002
DOI: 10.1046/j.1439-0523.2002.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of Brassica juncea×Brassica rapa hybrids and patterns of variation in the hybrid derivatives

Abstract: Interspecific hybridization is an important tool to elucidate intergenomic relationships, transfer characters across species and develop synthetic amphidiploids, and it has been widely applied for improving brassicas. The objective of the present study was to create genetic variability in Brassica through interspecific hybridization. Crosses between Brassica juncea (AABB, 2n ¼ 36), and Brassica rapa (AA, 2n ¼ 20) vars toria, yellow sarson, and brown sarson were attempted, and the hybrid derivatives were advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Choudhary et al (2002) also reported a high frequency of the maternal and intermediate types of plants in F 2 generation of B. juncea  B. rapa crosses. Wide phenotypic variation and transgressive segregation for plant height, primary branches per plant, main raceme length, siliquae on main raceme and seed yield per plant in the F 2 generation might have resulted from recombination and or eventual segregation of aneuploid forms arising in the populations.…”
Section: F 2 Generationmentioning
confidence: 87%
See 2 more Smart Citations
“…Choudhary et al (2002) also reported a high frequency of the maternal and intermediate types of plants in F 2 generation of B. juncea  B. rapa crosses. Wide phenotypic variation and transgressive segregation for plant height, primary branches per plant, main raceme length, siliquae on main raceme and seed yield per plant in the F 2 generation might have resulted from recombination and or eventual segregation of aneuploid forms arising in the populations.…”
Section: F 2 Generationmentioning
confidence: 87%
“…Prakash (1973) succeeded in obtaining some high-yielding physiological variants from segregants of the B. campestris  B. nigra cross. Similarly, Rao et al (1993) and Choudhary et al (2002) obtained transgressive segregants for yield components from the F 2 generation of B. napus  B. carinata and B. juncea  B. rapa crosses, respectively. Thus present study indicated that interspecific hybridization in Brassica could be a valuable source for generating variability.…”
Section: F 2 Generationmentioning
confidence: 91%
See 1 more Smart Citation
“…Olsson (1960aOlsson ( , 1960b) also found wide variation in plant height, flowering and maturity, siliqua size, and pollen fertility in F 2 and F 3 plants of the cross B. rapa B. nigra. Similarly, Rao et al (1993) and Choudhary et al (2002) obtained transgressive segregants for yield components from the F 2 generation of B. napus B. carinata and B. juncea B. rapa crosses, respectively. Non-homologous pairing and the resultant exchange between chromosomes of different genomes would play an important role for creating a wide range of variability (Prakash 1973b), and thus provide immense opportunity for broadening the gene pool in the genus Brassica.…”
Section: Mizushima 1952)mentioning
confidence: 91%
“…The simplest method to evaluate male fertility is pollen staining with traditional stains like aceto-carmine and acid fuchsin (e.g., Choudhary et al, 2002;Chen et al, 2003;Matsuoka et al, 2007). This allows a rapid confirmation of pol-len sterility, often accompanied with indehiscence of anthers in totally sterile hybrids.…”
Section: Fertility Of Hybrids (And Their Progenies)mentioning
confidence: 99%